2014
DOI: 10.1590/0004-282x20140135
|View full text |Cite
|
Sign up to set email alerts
|

Cauda equina redundant nerve roots are associated to the degree of spinal stenosis and to spondylolisthesis

Abstract: To evaluate the association of redundant nerve roots of cauda equina (RNRCE) with the degree of lumbar spinal stenosis (LSS) and with spondylolisthesis. Method: After Institutional Board approval, 171 consecutive patients were retrospectively enrolled, 105 LSS patients and 66 patients without stenosis. The dural sac cross-sectional area (CSA) was measured on T2w axial MRI at the level of L2-3, L3-4 and L4-5 intervertebral discs. Two blinded radiologists classified cases as exhibiting or not RNRCE in MRI. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…1). In the remaining 40% of patients, redundant nerve roots (RNRs) of the cauda equina are evident on preoperative magnetic resonance images (MRIs) [2][3][4][5]. RNRs were first described by Verbiest [6] in 1954, and they were named 14 years later by Cressman and Pawl [7].…”
Section: Introductionmentioning
confidence: 99%
“…1). In the remaining 40% of patients, redundant nerve roots (RNRs) of the cauda equina are evident on preoperative magnetic resonance images (MRIs) [2][3][4][5]. RNRs were first described by Verbiest [6] in 1954, and they were named 14 years later by Cressman and Pawl [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of RNRs in patients with lumbar spinal canal stenosis varied from 15% to 42% . The prevalence of RNRs in patients without spinal canal stenosis was reported as 9%, which is significantly lower than that in patients with spinal stenosis (41%) . Furthermore, the severity of lumbar spinal canal stenosis was demonstrated as a risk factor for RNRs .…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence of RNRs in patients without spinal canal stenosis was reported as 9%, which is significantly lower than that in patients with spinal stenosis (41%) . Furthermore, the severity of lumbar spinal canal stenosis was demonstrated as a risk factor for RNRs . The pathogenesis of RNRs is still unclear, and it has been suggested that RNRs are associated with damaged nerve roots and impaired nerve–blood barrier resulting from spinal canal constriction .…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Redundant nerve root is a complication that arises as a result of continuous and chronic compressive forces on the nerve roots within the canal of a CLDCS. Chronic lumbar degenerative canal stenosis is the result of degenerative narrowing of the lumbar spinal canal caused by bulging of an intervertebral disk, osseous hypertrophy of the vertebral neural arch, apophyseal joint arthrosis, ligamentum flavum hypertrophy, and/or degenerative spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of RNR varies, with some observing it in 33.8% to 42% of patients with CLDCS. 1 There is no statistical gender difference for RNR. 7 The purpose of this case study was to present the diagnostic imaging findings of a patient with CLDCS with associated redundant nerve roots.…”
Section: Introductionmentioning
confidence: 99%